Integration of storage and renewable energy into district heating systems: A review of modelling and optimization. (15th October 2016) - Olsthoorn, Dave; Haghighat, Fariborz; Mirzaei, Parham A.
Highlights: District heating systems (DHS) is a promising technology to address sustainability in buildings. Modelling methods were discussed in terms of computation, precision and degree of output certainty. DHS are classified in terms of optimization objectives. Research limitations were summarized and future research directions were proposed. Abstract: The building and infrastructure sector is accountable for 46% of the total worldwide energy consumption. Most traditional energy sources such as coal or petroleum are among the non-renewable types and most likely to be depleted in the forthcoming decades. To address the current energy crisis, use of renewable energy such as solar sources and a considerable increase in energy efficiency are proposed as the potential solutions. District heating systems (DHS), in particular, has recently received more attention due to several advantages in energy production, distribution and consumption for the space heating. This paper reviews the recent advancements in the energy production, modelling and optimization of the DHSs. A classification of energy sources is presented in terms of their sustainability and ease of integration to a DHS. Current modelling methods are further compared with respect to computational limitations, level of precision as well as the degree of certainty in the output level. Moreover, the recent studies of DHS are classified in accordance with the optimization objectives, including energy/exergy efficiency, cost, exergo-economic/thermo-economic and green-house gas (GHG) and pollutant production.